Effect of Bud Load and Rootstock Cultivar on the Performance of V. vinifera L. cv. Red Muscadel (Muscat noir) - Archer, E.; Fouche, G.W. (South African Journal of Enology and Viticulture, 2017)
The effect of four different bud loads and six rootstock cultivars on the performance of V. vinifera L. cv. Red Muscadel (Muscat noir) was investigated. Parameters such as yield, cane, cluster and berry mass, budding percentage, bud fertility, leaf surface area, grape composition and wine quality were measured in an effort to establish the best root-stock and bud load for this cultivar. Both bud load and rootstock cultivar had significant effects on all parameters measured. The effect of bud loads depended on the rootstock cultivar used. Considering all parameters, the rootstock cultivars 110 Richter and Ramsey showed the best performance.